The refiner's fire: the making of Mormon cosmology, 1644-1844 - Brooke, John L. (Cambridge University Press, 1994)
This 1995 book presents an alternative and comprehensive understanding of the roots of Mormon religion, which proposes that the faithful will become gods. The book's central thesis is that the origins of Mormonism lie in the fusion of radical religion with magical ideas about recovering the divine powers of Adam lost in the fall from Paradise (ideas known as the hermetic philosophy) that occurred during the Reformation and the English Revolution. The book is organised around the two problems of demonstrating the survival of these ideas into the nineteenth century and of how they were manifested in Mormon doctrine. A final chapter outlines how Mormonism gradually has moved toward traditional Protestant Christianity since the 1850s. Besides religion, this book deals with magic, witchcraft, alchemy, Freemasonry, counterfeiting, and state-formation.